The Effect of Science, Technology, Engineering, and Mathematics (STEM) Learning on Students’ Problem Solving Skill - Fathiah Alatas; Nur Afriyati Yakin (STKIP Singkawang, 2021)
Problem solving is one of the abilities that must be mastered in the 21st century, lack of mastery of students’ concepts in work and energy material has an impact on students' problem solving abilities. This research aims to measure students' problem solving skill on work and energy material. The research was used quasi-experiment with the design of a nonequivalent control group design. The subject of the research consist of 70 students at the 10th grade of one of high school in Kabupaten Tangerang with technique was used purposive sampling. The research used 10 essay questions as test instrument problem solving skill with 5 indicators of problem solving skill, namely visualize the problem, describe the problem in physics description, plan the solution, execute the plan and check and evaluate. The research result shows that is a effect of STEM learning on student’s problem solving skill proven by student’s problem solving skill of the experimental group increased higher (N-Gain 0.71 high category) compares to the control group (N-Gain 0,38 middle category).